The authority trap : strategic choices of international NGOs - Stroup, Sarah S. (Sarah Snip), 1978-; Wong, Wendy H., 1980- (Cornell University Press, 2017)
Not all international nongovernmental organizations (INGOs) are created equal. Some have emerged as "leading INGOs" that command deference from various powerful audiences and are well-positioned to influence the practices of states, corporations, and other INGOs. Yet Sarah S. Stroup and Wendy H. Wong make a strong case for the tenuous nature of the position: in order to retain their authority, INGOs such as Greenpeace, Oxfam, and Amnesty International refrain from expressing radical opinions that could severely damange their long-term reputation. Stroup and Wong contend such INGOs must constantly adjust their behavior to maintain a delicate equilibrium that preserves their status. Activists, scholars, and students seeking to understand how international organizations garner and conserve power - and how this affects their ability to fulfill their stated missions - will find much of value in The Authority Trap. -- from back cover